COOPERATIVE PRINCIPLE USED BY PATRICK STARRR AND THE GUEST STARS IN BEAUTY VLOGS - Ayuningsih, Katerina (Seminar Nasional Ilmu Terapan, 2019)
Beauty vlogs in YouTube have the most viewers which are 125 billion in 2016 (Pixability, 2016). Among beauty vloggers, Patrick Starrr is quite well-known. He produces quite interesting vlogs by inviting celebrities as his guest stars, such as Kim Kardashian, Katy Perry, and Kris Jenner. During the conversation, Patrick takes the leading role by asking questions and also cracks some jokes which were sometimes responded by the guest stars accordingly. Thus, the main objectives of this research were (i) to find out the cooperative principle applied by Patrick Starrr and the guest stars in beauty vlogs and (ii) to find out the maxim which flouted by Patrick Starrr and the guest star in beauty vlogs. This research is used qualitative case study research. It is found that there were four maxims of cooperative principle applied by Patrick Starrr and the guest stars. From those maxims, the maxim of relation was the mostly applied maxim in beauty vlogs. It is also found that there were four maxims of cooperative principle flouted by Patrick Starrr and the guest stars. From those flouting maxims, the maxim of quantity was the mostly flouted maxim in beauty vlogs.